Dinâmicas territoriais e os corredores verdes como modelos de estruturação espacial urbana: abordagens inter-relacionais na cidade de Araraquara-SP - Menzori, Ivan Damasco (Universidade Federal de São Carlos, 2018)
In Brazil, the appropriation of city by the urban-legal order is inserted in a scenario of recurring conflicts of interest. Practices of city production reveal experiences with economic interests strongly linked to the dynamics of urban growth. The establishment of this scenario favored the practices of capital reproduction through real estate speculation, in which urban sprawl provides new urbanized peripheries, which invade the greenbelts while reserving well-located, empty or underused urban voids, for the extraction of capital gains. Thus, new urbanized areas, even more distant, draw the boundaries for the urban territory and the reproduction of real estate capital, fragmenting the urban vegetation and compromising its environmental functions. In this theme and context, the intent of this research is associated to contributing to the knowledge of the territorial dynamics, with an integrated and transdisciplinary approach, in the ambit of the urban environmental planning of Araraquara city. The analyzes contemplated the urban environmental zoning of the 2005 Master Plan (PD) and its compact and sustainable city production strategies, as well as detailed analyzes of land use and land cover of urban green infrastructures represented by Ecological Integration Corridors (Ciecos), of the urban evolution of Araraquara, and the urban insertion of Special Areas of Social Interest (AEIS), in order to provide comparisons and diagnoses between the current situation of the aforementioned elements with the most up-to-date physical bases, representative of the most notable environmental vulnerabilities. The results indicate that since 2014, with the revocation followed by a review of the master plan, several areas of environmental control had their parameters changed, or suffered considerable reductions, turning irresolute the land use and land cover guidelines. Moreover, analyzes show expansionist strategies towards an extremely peripheral, environmentally vulnerable region characterized by gentrification and socio-spatial segregation through clusters of low-income social housing units, antagonizing the precepts of the City Statute. Regarding the Ciecos’ mapping, it was identified that 81.6% of the Permanent Preservation Areas (APPs) and 59.6% of Ciecos did not present characteristics of recent anthropic use. And the transdisciplinary analyzes on the territorial dynamics, focusing on the Ciecos as an open space system and green infrastructure, continued to show the current conjuncture of the territory within several fields of knowledge in Urban Engineering, listing the main socio-environmental weaknesses and threats of the urban context, as well as strengths and opportunities intrinsic to the Ciecos, that can incite a course correction as powerful agents of change and a source of progress in the urban life.
Territorial dynamics and green corridors as urban spatial structuring models: inter-relational approaches in Araraquara city
Keywords: Planejamento ambiental urbano; Corredores verdes; Dinâmicas territoriais; Urban environmental planning; Green corridors; Territorial dynamics; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; ENGENHARIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL